Metallic texture interior wall decorative plate and preparation method thereof
Patent Information
- Application Number
- CN202610160516.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-04
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-02-04
AI Technical Summary
[0005]针对现有技术中金属饰面与无机基板因界面粘结不牢导致的易剥离、鼓包等问题,本申请提供一种金属质感内墙装饰板及其制备方法
本申请通过在基板与铝饰面层之间构建增渗层与胶黏层的复合界面体系:增渗层凭借低分子量树脂的渗透性及硅烷偶联剂的化学键合,实现了与无机基板的高强度结合;胶黏层则利用高柔韧性聚氨酯的应力缓冲能力,有效消解了因材料热膨胀系数差异产生的内应力。两者功能互补、协同作用,共同确保了装饰板的层间结合强度与整体结构稳定性。
Abstract
Description
Technical Field
[0001] This application relates to the technical field of building decoration materials, and more specifically, it relates to a metallic-textured interior wall decoration panel and its preparation method. Background Technology
[0002] With the acceleration of urbanization and the increasing demand for high-quality, aesthetically pleasing, and environmentally friendly materials in the building decoration industry, the market demand for metal decorative panels, as an important material in modern building decoration, continues to expand. Currently, most mainstream products are composites made by bonding inorganic substrates such as calcium silicate boards and cement fiber boards with metal finishes such as aluminum plates using adhesives. Due to the low porosity, low surface energy, and strong chemical inertness of substrates such as calcium silicate boards, ordinary adhesives are difficult to use for strong wetting and anchoring. Existing technologies typically employ physical grinding, adding physical leveling layers, or using highly polar adhesives to attempt to improve adhesion. However, in the long run, under the cyclical changes in indoor temperature and humidity, the internal stress caused by the difference in thermal expansion coefficients between the substrate and the finish layer, as well as the aging of the adhesive layer itself, can still easily lead to interface failure, resulting in problems such as blistering and peeling of the finish layer, affecting both decorative effect and safety.
[0003] Patent application CN121019055A discloses a hot-pressed aluminum composite decorative panel, comprising, from top to bottom, an aluminum decorative panel, an adhesive layer, a pull-out strength enhancement layer, and a calcium silicate board. The pull-out strength enhancement layer includes a reinforcing layer and a leveling layer. The thickness of the reinforcing layer is less than or equal to the thickness of the calcium silicate board. The reinforcing layer is located within the base layer, and the leveling layer is located between the adhesive layer and the calcium silicate board. The bottom surface of the aluminum decorative panel is bonded to the upper surface of the adhesive layer, the lower surface of the adhesive layer is bonded to the leveling layer, and the lower surface of the leveling layer is simultaneously bonded to the reinforcing layer and the calcium silicate board. While this design incorporates a pull-out strength enhancement layer (reinforcing layer + leveling layer) to improve adhesion, this structure only provides physical leveling and simple reinforcement. Long-term use still easily leads to problems such as interlayer delamination and aluminum plate bulging. Furthermore, the pull-out strength enhancement layer has a complex structure and a cumbersome manufacturing process.
[0004] Patent application CN111761889A discloses a three-dimensional metallic-finished integrated insulation and decorative panel. Its features include a substrate, an insulation board, a clear primer layer, a molding paint layer, a colored primer layer, and a metallic topcoat layer. The clear primer layer, molding paint layer, colored primer layer, and metallic topcoat layer sequentially cover one side of the substrate, and the other side of the substrate is connected to the insulation board. The clear primer layer is a two-component water-based epoxy coating; the molding paint layer is made of molding paint, which includes a masterbatch and sand; the colored primer layer is a two-component water-based polyurethane coating; and the metallic topcoat layer is a two-component water-based polyurethane coating. This design uses a multi-layered paint application to achieve the metallic finish. However, the paint layers adhere to the substrate surface and are susceptible to peeling, flaking, and blistering due to long-term temperature and humidity changes. Summary of the Invention
[0005] In view of the problems of easy peeling and bulging caused by poor interfacial bonding between metal veneer and inorganic substrate in the prior art, this application provides a metallic textured interior wall decoration panel and its preparation method.
[0006] In the first aspect, this application provides a metallic-textured interior wall panel, which adopts the following technical solution: A metallic-textured interior wall panel comprises, from bottom to top, a substrate, a diffusion-enhancing layer, an adhesive layer, and a metallic finish layer. The preparation of the permeation-enhancing layer includes the following raw materials in parts by weight: 80-120 parts of modified polyurethane resin, 40-60 parts of self-crosslinking silicone-acrylic emulsion, 4-8 parts of nano-silica, 40-60 parts of reactive diluent, 3-6 parts of silane coupling agent, 2-4 parts of organofluorine compound, 3-5 parts of curing agent A, 2-4 parts of photoinitiator, 2-4 parts of dispersant and 1-2 parts of defoamer; The preparation of modified polyurethane resin includes the following raw materials in parts by weight: The composition includes 70-80 parts of oligomeric polyol, 17-31 parts of diisocyanate, 15-20 parts of bisphenol A epoxy resin, 1.7-11 parts of polyhydroxy acrylate monomer, 0.05-0.1 parts of organotin catalyst, and 0.02-0.06 parts of polymerization inhibitor. The adhesive layer is prepared by means of the following raw materials in parts by weight: Component A: 70-85 parts of polyether-type polyurethane prepolymer, 5-10 parts of tackifier, 2-4 parts of antioxidant, 3-6 parts of toughening agent, and 0.07-0.1 parts of organotin catalyst; Component B: 8.5-13 parts of polyetheramine, 4-5.5 parts of adipate dihydrazide and 0.1-0.15 parts of 2-ethyl-4-methylimidazole.
[0007] In this technical solution, a composite interface system consisting of a permeation layer and an adhesive layer is constructed between the inorganic substrate and the aluminum veneer layer to synergistically achieve a stable interlayer bond. The permeation layer, utilizing a low-viscosity modified resin system, penetrates into the substrate micropores and forms a dense cross-linked network through photo-thermal dual curing. Simultaneously, a silane coupling agent enables chemical bonding with the substrate, thus completing the initial strengthening from physical anchoring to chemical bonding. The adhesive layer leverages the rapid curing characteristic of polyurethane under hot pressure to achieve high-strength adhesion to the upper and lower interfaces. Furthermore, the flexible segments of the polyether-type polyurethane effectively absorb and dissipate internal stresses caused by differences in the thermal expansion coefficients of the materials. Together, these two components ensure the interlayer bond strength and overall structural stability of the decorative panel.
[0008] Preferably, the method for preparing the modified polyurethane resin includes the following steps: Under an inert atmosphere, oligomeric polyol, diisocyanate and organotin catalyst are mixed evenly, heated to 70-75℃, reacted for 4-5 hours, cooled to 60-65℃, bisphenol A type epoxy resin is added, reacted for 2-2.5 hours, cooled, polyhydroxy acrylate monomer and polymerization inhibitor are added, heated to 65-70℃, reacted for another 5-6 hours, cooled, and modified polyurethane resin is obtained.
[0009] Preferably, the oligomeric polyol is at least one of polyether polyol and polyester polyol, and its number average molecular weight is not higher than 1000.
[0010] Preferably, the polyhydroxy acrylate monomer is pentaerythritol triacrylate.
[0011] Preferably, the organotin catalyst is dibutyltin dilaurate.
[0012] In this technical solution, firstly, the mechanical strength of the resin is improved by chemically grafting rigid epoxy segments; secondly, by introducing photocurable multifunctional acrylate groups, the resin can form a three-dimensional network with high cross-linking density during UV curing, thereby obtaining higher mechanical strength.
[0013] Preferably, the raw materials of the modified polyurethane resin further include 2 to 4 parts by weight of phosphate ester-containing acrylate monomers.
[0014] Preferably, in the method for preparing the modified polyurethane resin, after adding the polyhydroxy acrylate monomer, the method further includes the step of adding an acrylate monomer containing a phosphate ester.
[0015] Preferably, the phosphate-containing acrylate monomer is methacryloyloxyethyl phosphate.
[0016] In this technical solution, the phosphate-containing acrylate monomer introduced can introduce its phosphate groups into the polymer chain after participating in resin copolymerization. These groups can form a strong polar interaction with hydroxyl groups and other groups on the surface of the inorganic substrate, thereby introducing additional bonding force at the resin-substrate interface.
[0017] Preferably, the solid content of the self-crosslinking silicone-acrylic emulsion is 40%~50%, and the glass transition temperature is not higher than 10°C.
[0018] In this technical solution, during the water evaporation and film formation process of the emulsion, the active silanol groups on its molecular chain can undergo a condensation reaction to form a stable siloxane crosslinking network. This crosslinking structure can significantly improve the hardness and mechanical strength of the coating, and also enhance the water resistance and heat resistance of the coating itself. These improved properties help to enhance the coating's tolerance to changes in temperature and humidity.
[0019] Preferably, the bisphenol A type epoxy resin is epoxy resin E-51.
[0020] In this technical solution, bisphenol A type epoxy resin E-51 with low molecular weight and moderate viscosity is selected. It can undergo a grafting reaction with polyurethane prepolymer, thereby introducing rigid epoxy segments into the polyurethane network through chemical bonds. This structural design effectively increases the crosslinking density of the resin matrix, resulting in a significant enhancement in the mechanical strength of the modified resin.
[0021] Preferably, the reactive diluent is either isobornyl acrylate or tripropylene glycol diacrylate.
[0022] In this technical solution, the viscosity of the system is effectively reduced during the construction phase, thereby enhancing the wetting and penetration ability of the components in the permeation layer onto the calcium silicate board substrate. In the subsequent UV curing stage, the acrylate double bonds in their molecules can participate in the free radical polymerization reaction initiated by the photoinitiator, copolymerizing with components such as modified polyurethane resin to become part of the final cured network.
[0023] Preferably, the silane coupling agent is selected from at least one of silane coupling agent KH550 and silane coupling agent KH560.
[0024] Preferably, the organofluorine compound is perfluorooctyltriethoxysilane.
[0025] In this technical solution, the perfluoroalkyl chain can endow the coating with durable hydrophobic and oleophobic properties; while the silaneoxy group at its end can be hydrolyzed after application, and then undergo a condensation reaction with the active groups on the coating network and substrate surface to form chemical bonds, thereby stably anchoring the hydrophobic function at the interface.
[0026] Preferably, the curing agent A is an epoxy curing agent.
[0027] In this technical solution, during the thermosetting stage, the epoxy curing agent promotes the cross-linking reaction of the epoxy groups introduced in the modified polyurethane resin, and together with the acrylate network formed by UV curing, they construct an interpenetrating network structure, thereby enhancing the mechanical strength and adhesion durability of the permeation layer.
[0028] Preferably, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0029] Preferably, the dispersant is sodium polycarboxylate.
[0030] Preferably, the defoamer is an organosilicone defoamer.
[0031] Preferably, the polyether-type polyurethane prepolymer is a polyether-type MDI-terminated polyurethane prepolymer with an NCO content of 10% to 15%.
[0032] In this technical solution, on the one hand, the appropriate NCO content ensures that the prepolymer has sufficient chemical reactivity, enabling it to efficiently crosslink with the curing agent in component B and the active hydrogen groups on the interface to form a strong and tough polyurethane film; on the other hand, this content range allows the adhesive to maintain suitable initial viscosity and open time while possessing high final bond strength, thereby achieving good coating operability and sufficient interface wetting in the hot-pressing composite process.
[0033] Preferably, the tackifier is a petroleum resin.
[0034] In this technical solution, during the construction phase, petroleum resin can effectively reduce the viscosity of the adhesive, improve its wetting and spreading ability on the surfaces of the penetration layer and the metal finish layer, thereby enhancing initial adhesion. After curing, petroleum resin, as a non-reactive component, is dispersed in the polyurethane film, which can adjust the modulus and toughness of the adhesive layer, helping to improve the flexibility and stress distribution of the adhesive layer while maintaining sufficient bond strength.
[0035] Preferably, the antioxidant is antioxidant 1010.
[0036] Preferably, the toughening agent is polyamide wax micro powder.
[0037] In this technical solution, polyamide wax micropowder acts as a toughening agent, which can be uniformly dispersed in the adhesive film after the adhesive has cured. Its addition can effectively improve the toughness, peel resistance, and impact resistance of the cured adhesive layer without significantly sacrificing the modulus and bond strength of the adhesive layer.
[0038] Preferably, the metal finish layer comprises, from bottom to top, a metal base layer, a white adhesive layer, a transfer film layer, and an elastic topcoat layer.
[0039] Preferably, the thickness of the metal base layer is 0.5~1.0 mm.
[0040] Preferably, the white glue layer is made from environmentally friendly white latex and has a thickness of 10~15μm; Preferably, the elastic topcoat layer is a water-based polyurethane topcoat with a thickness of 10~15μm.
[0041] Preferably, the substrate is an asbestos-free fiber calcium silicate board with a thickness of 5-12 mm.
[0042] More preferably, the substrate is an asbestos-free fiber calcium silicate board with a thickness of 5-8 mm.
[0043] Secondly, this application provides a method for preparing a metallic-textured interior wall decorative panel, comprising the following steps: S1: After mixing nano-silica, dispersant and part of reactive diluent, add modified polyurethane resin, self-crosslinking silicone-acrylic emulsion, the remaining reactive diluent, silane coupling agent, organofluorine compound and defoamer, add curing agent A and photoinitiator, mix evenly to obtain the penetration-enhancing coating. S2: At 90~100℃, the polyether-type polyurethane prepolymer, tackifier, antioxidant, toughening agent and organotin catalyst are mixed evenly to obtain component A; the polyetheramine, adipate dihydrazide and 2-ethyl-4-methylimidazolium are mixed evenly to obtain component B; before use, component A and component B are mixed evenly to obtain the adhesive. S3: After pretreating the substrate, the infiltration layer coating is evenly applied to the substrate surface and cured to obtain the infiltration layer; S4: Apply adhesive to the surface of the permeation layer, attach the metal finishing layer, hot-press to bond, and then perform post-treatment to obtain the final product.
[0044] Preferably, the coating amount of the penetration-enhancing layer is 100~150g / m². 2 .
[0045] Preferably, the curing process includes sequential UV curing and thermal curing.
[0046] Preferably, the thermosetting temperature is 80~85℃ and the time is 30~40min.
[0047] Preferably, the coating amount of the adhesive is 150~200g / m². 2 .
[0048] Preferably, the hot pressing parameters are: pressure of 0.8~1.0MPa, temperature of 90~120℃, and time of 10~12min.
[0049] In this technical solution, the substrate surface is first pretreated and coated with a permeation-enhancing layer. By first curing with UV light and then with heat, the components of the permeation-enhancing layer are rapidly shaped and fully cross-linked, forming a strong and tough transition layer that is chemically anchored to the substrate. Subsequently, a highly reactive polyurethane adhesive is applied and laminated with an aluminum finish layer. Under hot pressing conditions, the adhesive layer itself is fully cured and forms a strong bond with the underlying permeation-enhancing layer and the upper aluminum finish layer.
[0050] In summary, this application has the following beneficial effects: This application constructs a composite interface system of a permeation layer and an adhesive layer between the substrate and the aluminum veneer layer. The permeation layer achieves a high-strength bond with the inorganic substrate through the permeability of the low molecular weight resin and the chemical bonding of the silane coupling agent. The adhesive layer effectively dissipates the internal stress caused by the difference in the thermal expansion coefficients of the materials by utilizing the stress-buffering capacity of highly flexible polyurethane. The two layers complement each other and work synergistically to ensure the interlayer bonding strength and overall structural stability of the decorative panel. Detailed Implementation
[0051] The present application will be further described in detail below with reference to the embodiments.
[0052] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.
[0053] The solid content of the self-crosslinking silicone-acrylic emulsion is 40%~50%, and the glass transition temperature is not higher than 10℃.
[0054] Preparation Examples 1-5: Modified Polyurethane Resins Preparation Example 1 The preparation method of the modified polyurethane resin in this example includes the following steps: Under a nitrogen atmosphere, 700g of polyethylene adipate (number average molecular weight 1000), 168g of isophorone diisocyanate, and 0.5g of dibutyltin dilaurate were added sequentially to a dry reactor. The mixture was heated to 70°C and stirred for 4 hours. The temperature was then lowered to 60°C, and 150g of epoxy resin E-51 (hydroxyl content 0.5%) was added. The mixture was kept at this temperature and stirred for 2 hours. The temperature was then lowered to 50°C, and 17.3g of pentaerythritol triacrylate and 0.2g of p-hydroxyanisole were added. The temperature was then raised to 70°C, and the mixture was stirred for another 5 hours until the NCO content was below 0.5%. Heating was then stopped, and the mixture was cooled to room temperature to obtain the modified polyurethane resin.
[0055] In this preparation example, the initial molar ratio (R value) of isocyanate groups to total hydroxyl groups is approximately 1.00.
[0056] Preparation Example 2 The preparation method of the modified polyurethane resin in this example includes the following steps: Under a nitrogen atmosphere, 800g of polypropylene glycol (number average molecular weight 600), 310g of isophorone diisocyanate, and 1.0g of dibutyltin dilaurate were added sequentially to a dry reactor. The mixture was heated to 75°C and stirred for 5 hours. The temperature was then lowered to 65°C, and 200g of epoxy resin E-51 (hydroxyl content 0.5%) was added. The mixture was kept at this temperature and stirred for 2.5 hours. The temperature was then lowered to 50°C, and 19g of pentaerythritol triacrylate and 0.2g of p-hydroxyanisole were added. The temperature was then raised to 65°C, and the mixture was stirred for another 6 hours until the NCO content was below 0.5%. Heating was then stopped, and the mixture was cooled to room temperature to obtain the modified polyurethane resin.
[0057] In this preparation example, the initial molar ratio (R value) of isocyanate groups to total hydroxyl groups is approximately 1.00.
[0058] Preparation Example 3 The preparation method of the modified polyurethane resin in this example includes the following steps: Under a nitrogen atmosphere, 400g of polybutylene adipate (number average molecular weight 1000), 400g of polypropylene glycol (number average molecular weight 600), 260g of isophorone diisocyanate, and 0.9g of dibutyltin dilaurate were added sequentially to a dry reactor. The mixture was heated to 75°C and stirred for 4.5h. The temperature was then lowered to 65°C, and 180g of epoxy resin E-51 (hydroxyl content 0.5%) was added. The mixture was kept at this temperature and stirred for 2.5h. The temperature was then lowered to 50°C, and 74.6g of pentaerythritol triacrylate and 0.5g of p-hydroxyanisole were added. The temperature was then raised to 65°C, and the mixture was stirred for another 5.5h until the NCO content was below 0.5%. Heating was then stopped, and the mixture was cooled to room temperature to obtain the modified polyurethane resin.
[0059] In this preparation example, the initial molar ratio (R value) of isocyanate groups to total hydroxyl groups is approximately 0.96.
[0060] Preparation Example 4 The preparation method of the modified polyurethane resin in this example includes the following steps: Under a nitrogen atmosphere, 400g of polybutylene adipate (number average molecular weight 1000), 400g of polypropylene glycol (number average molecular weight 600), 310g of isophorone diisocyanate, and 0.9g of dibutyltin dilaurate were added sequentially to a dry reactor. The mixture was heated to 75°C and stirred for 4.5h. The temperature was then lowered to 65°C, and 180g of epoxy resin E-51 (hydroxyl content 0.5%) was added. The mixture was kept at this temperature and stirred for 2.5h. The temperature was then lowered to 50°C, and 113g of pentaerythritol triacrylate, 20g of 2-hydroxyethyl methacrylate phosphate, and 0.6g of p-hydroxyanisole were added. The temperature was slowly raised to 65°C, and the mixture was stirred for another 6h until the NCO content was below 0.5%. Heating was then stopped, and the mixture was cooled to room temperature to obtain the modified polyurethane resin.
[0061] In this preparation example, the initial molar ratio (R value) of isocyanate groups to total hydroxyl groups is approximately 1.02.
[0062] Preparation Example 5 The preparation method of the modified polyurethane resin in this example includes the following steps: Under a nitrogen atmosphere, 400g of polybutylene adipate (number average molecular weight 1000), 400g of polypropylene glycol (number average molecular weight 600), 310g of isophorone diisocyanate, and 0.9g of dibutyltin dilaurate were added sequentially to a dry reactor. The mixture was heated to 75°C and stirred for 4.5h. The temperature was then lowered to 65°C, and 180g of epoxy resin E-51 (hydroxyl content 0.5%) was added. The mixture was kept at this temperature and stirred for 2.5h. The temperature was then lowered to 50°C, and 55g of pentaerythritol triacrylate, 40g of 2-hydroxyethyl methacrylate phosphate, and 0.4g of p-hydroxyanisole were added. The temperature was slowly raised to 65°C, and the mixture was stirred for another 6h until the NCO content was below 0.5%. Heating was then stopped, and the mixture was cooled to room temperature to obtain the modified polyurethane resin.
[0063] In this preparation example, the initial molar ratio (R value) of isocyanate groups to total hydroxyl groups is approximately 1.03.
[0064] Example 1 The metallic interior wall panel of this embodiment includes, from bottom to top, a substrate, a permeation layer, an adhesive layer, and an aluminum veneer layer. The permeation layer is prepared by the following raw materials in parts by weight: 800g modified polyurethane resin, 400g self-crosslinking silicone-acrylic emulsion, 40g nano silica, 400g reactive diluent, 30g silane coupling agent, 20g organic fluoride, 30g curing agent A, 20g photoinitiator, 20g dispersant, and 10g defoamer. The substrate is an asbestos-free fiber calcium silicate board with a thickness of 5mm. The modified polyurethane resin was derived from Preparation Example 1. The self-crosslinking silicone-acrylic emulsion had a solid content of 40% and a nano-silica particle size distribution of 1-50 nm. The reactive diluent was isobornyl acrylate, the silane coupling agent was silane coupling agent KH550, the organofluorine compound was perfluorooctyltriethoxysilane, the curing agent A was epoxy curing agent T31, the photoinitiator was 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, the dispersant was sodium polyacrylate with a solid content of 40%, and the defoamer was an organosilicon defoamer with a solid content of 30%.
[0065] The adhesive layer is prepared by means of the following raw materials in parts by weight: Component A: 700g polyether polyurethane prepolymer, 50g tackifier, 20g antioxidant, 30g toughening agent, and 0.7g dibutyltin dilaurate; Component B: 85g of polyetheramine 230, 40g of adipate dihydrazide, and 1.2g of 2-ethyl-4-methylimidazole.
[0066] Among them, the polyether-type polyurethane prepolymer is a polyether-type MDI-terminated polyurethane prepolymer with an NCO content of 10% by mass; the tackifier is hydrogenated C9 petroleum resin with a softening point of 85℃; the antioxidant is antioxidant 1010; and the toughening agent is polyamide wax micro powder with a particle size of 1~5μm.
[0067] This embodiment also provides a method for preparing a metallic-textured interior wall decorative panel, including the following steps: S1: Add nano-silica, dispersant and 50% of the total mass of reactive diluent to a high-speed disperser, adjust the speed to 2000 r / min, disperse for 30 min, then add modified polyurethane resin, self-crosslinking silicone-acrylic emulsion, the remaining reactive diluent, silane coupling agent, organofluorine compound and defoamer, adjust the speed to 1200 r / min, stir for 60 min, add curing agent A and photoinitiator, adjust the speed to 800 r / min, stir for 20 min, and obtain the penetration-enhancing coating layer; S2: Add the polyether-type polyurethane prepolymer to the reactor, heat to 90°C, add the pulverized thickener, stir for 30 min, add the antioxidant, toughening agent and dibutyltin dilaurate, adjust the speed to 1000 r / min, stir for 40 min, mix evenly to obtain component A; Polyetheramine 230, adipate dihydrazide and 2-ethyl-4-methylimidazolium were mixed evenly to obtain component B; Before use, mix component A and component B thoroughly to obtain the adhesive; S3: Mechanically roughen one side of the substrate to a depth of approximately 0.15±0.05mm. Wipe the surface with anhydrous ethanol to remove dust and oil. Dry in a 60℃ oven for 2 hours, then cool to room temperature. Use a scraper to evenly coat the penetration enhancement coating onto the roughened surface of the substrate with a coating amount of 100g / m². 2 Let stand for 15 minutes; then perform UV curing using a 365nm UV lamp with an irradiation intensity of 800mJ / cm². 2 Irradiate for 30 seconds; then place in an 80℃ oven for heat curing for 30 minutes. After heat curing, cool to room temperature and wipe the surface of the infiltration layer with acetone. If the surface is not sticky and the coating does not dissolve, the curing is considered to be up to standard; a uniform and dense infiltration layer is obtained. S4: Apply the adhesive evenly to the surface of the permeation-reinforcing layer, with a coating amount of 150g / m². 2The pre-treated aluminum veneer layer (the side away from the veneer layer) is aligned and bonded to the substrate coated with adhesive. It is then placed in a hot press for hot pressing and bonding. The hot pressing temperature is initially set to 90℃, the hot pressing pressure to 0.8MPa, and the hot pressing time to 5 minutes. Then, the temperature is increased to 120℃, the hot pressing pressure to 0.8MPa, and the hot pressing time to 5 minutes. After that, it is placed in an environment of 25℃ and 50% relative humidity for 72 hours for curing. Then, it is cut, the edges are polished, the surface is cleaned, and burrs and excess adhesive are removed to obtain a metallic interior wall decoration panel.
[0068] The method for preparing the aluminum veneer layer includes the following steps: A 0.5mm thick aluminum alloy plate is degreased and alkaline washed on both sides, then rinsed with pure water and dried. Environmentally friendly white latex (solid content approximately 45%) is evenly coated onto one side of the aluminum alloy plate using a roller coating method. The wet film thickness is controlled, and the plate is dried at 80℃ for 5 minutes to form a white adhesive layer with a thickness of approximately 10μm. A decorative PET heat transfer film (20μm thick) with a predetermined metallic pattern is then bonded to the white adhesive layer and fed into a hot press. The press is then hot-pressed at 120℃ and 0.6MPa for 60 seconds. After cooling, the PET base film is peeled off, and a water-based polyurethane topcoat is roller coated. The plate is then baked at 85℃ for 15 minutes to form an elastic topcoat layer with a thickness of 10μm, thus obtaining the aluminum decorative layer.
[0069] Test results: The obtained metallic interior wall decorative panels were subjected to flexural strength and tensile strength tests. According to GB / T 7019-2024, the test results showed that: the average dry flexural strength was 28.5 MPa; the average water-saturated flexural strength was 26.6 MPa; the average tensile strength was 0.95 MPa; and the maximum single tensile strength was 1.10 MPa.
[0070] Example 2 The metallic interior wall panel of this embodiment includes, from bottom to top, a substrate, a permeation layer, an adhesive layer, and an aluminum veneer layer. The preparation of the permeation layer includes the following raw materials in parts by weight: 1200g modified polyurethane resin, 600g self-crosslinking silicone-acrylic emulsion, 80g nano silica, 600g reactive diluent, 60g silane coupling agent, 40g organic fluoride, 50g curing agent A, 40g photoinitiator, 40g dispersant, and 20g defoamer. The substrate is an asbestos-free fiber calcium silicate board with a thickness of 8mm. The modified polyurethane resin was derived from Preparation Example 2. The self-crosslinking silicone-acrylic emulsion had a solid content of 50% and a nano-silica particle size distribution of 1-50 nm. The reactive diluent was tripropylene glycol diacrylate, the silane coupling agents included 30 g of silane coupling agent KH550 and 30 g of silane coupling agent KH560, the organofluorine compound was perfluorooctyltriethoxysilane, the curing agent A was epoxy curing agent T31, the photoinitiator was 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, the dispersant was sodium polyacrylate with a solid content of 40%, and the defoamer was an organosilicon defoamer with a solid content of 30%.
[0071] The adhesive layer is prepared by means of the following raw materials in parts by weight: Component A: 850g of polyether-type MDI-terminated polyurethane prepolymer, 100g of tackifier, 40g of antioxidant, 60g of toughening agent, and 1g of dibutyltin dilaurate; Component B: 103g of polyetheramine 230, 48.5g of adipic acid dihydrazide and 1.5g of 2-ethyl-4-methylimidazole.
[0072] Among them, the polyether-type polyurethane prepolymer is a polyether-type MDI-terminated polyurethane prepolymer with an NCO content of 10% by mass; the tackifier is hydrogenated C9 petroleum resin with a softening point of 85℃; the antioxidant is antioxidant 1010; and the toughening agent is polyamide wax micro powder with a particle size of 1~5μm.
[0073] This embodiment also provides a method for preparing a metallic-textured interior wall decorative panel, including the following steps: S1: Add nano-silica, dispersant and 50% of the total mass of reactive diluent to a high-speed disperser, adjust the speed to 2000 r / min, disperse for 30 min, then add modified polyurethane resin, self-crosslinking silicone-acrylic emulsion, the remaining reactive diluent, silane coupling agent, organofluorine compound and defoamer, adjust the speed to 1200 r / min, stir for 60 min, add curing agent A and photoinitiator, adjust the speed to 800 r / min, stir for 20 min, and obtain the penetration-enhancing coating layer; S2: Add the polyether-type polyurethane prepolymer to the reactor, heat to 100°C, add the pulverized thickener, stir for 30 min, cool to 45°C, add antioxidant, toughening agent and dibutyltin dilaurate, adjust the speed to 1000 r / min, stir for 40 min, mix evenly, and obtain component A. Polyetheramine 230, adipate dihydrazide and 2-ethyl-4-methylimidazolium were mixed evenly to obtain component B; Before use, mix component A and component B thoroughly to obtain the adhesive; S3: Mechanically roughen one side of the substrate to a depth of approximately 0.15±0.05mm. Wipe the surface with anhydrous ethanol to remove dust and oil. Dry in a 60℃ oven for 2 hours, then cool to room temperature. Use a scraper to evenly coat the penetration enhancement coating onto the roughened surface of the substrate with a coating amount of 150g / m². 2 Let stand for 25 minutes; then perform UV curing using a 365nm UV lamp with an irradiation intensity of 800mJ / cm². 2 Irradiation time is 40s; then it is placed in an 85℃ oven for heat curing for 40min. After heat curing, it is cooled to room temperature, and the surface of the infiltration layer is wiped with acetone. If the surface is not sticky and the coating does not dissolve, the curing is considered to be up to standard; a uniform and dense infiltration layer is obtained. S4: Apply the adhesive evenly to the surface of the permeation-reinforcing layer, with a coating amount of 200g / m². 2 The pre-treated aluminum veneer layer (the side away from the veneer layer) is aligned and bonded to the substrate coated with adhesive. It is then placed in a hot press for hot pressing and bonding. The hot pressing temperature is initially set to 90℃, the hot pressing pressure to 1.0MPa, and the hot pressing time to 7 minutes. Then, the temperature is increased to 120℃, the hot pressing pressure to 1.0MPa, and the hot pressing time to 5 minutes. After curing in an environment of 25℃ and 50% relative humidity for 72 hours, the surface is cut, ground, and cleaned to remove burrs and excess adhesive, resulting in a metallic interior wall decorative panel.
[0074] The method for preparing the aluminum veneer layer includes the following steps: A 1.0mm thick aluminum alloy plate is degreased and alkaline washed on both sides, then rinsed with pure water and dried. Environmentally friendly white latex (solid content approximately 45%) is evenly coated onto one side of the aluminum alloy plate using a roller coating method. The wet film thickness is controlled, and the plate is dried at 80℃ for 7 minutes to form a white adhesive layer with a thickness of approximately 15μm. A decorative PET heat transfer film (30μm thick) with a predetermined metallic pattern is then bonded to the white adhesive layer and fed into a hot press. The press is then hot-pressed at 120℃ and 0.6MPa for 60 seconds. After cooling, the PET base film is peeled off, and a water-based polyurethane topcoat is roller coated. The plate is then baked at 85℃ for 15 minutes to form an elastic topcoat layer with a thickness of 15μm, thus obtaining the aluminum decorative layer.
[0075] Test results: The obtained metallic interior wall decorative panels were subjected to flexural strength and tensile strength tests. According to GB / T 7019-2024, the test results showed that: the average dry flexural strength was 30.3 MPa; the average saturated flexural strength was 28.1 MPa; the average tensile strength was 1.05 MPa; and the maximum single tensile strength was 1.18 MPa.
[0076] Example 3 The difference between this embodiment and Embodiment 2 is as follows: The metallic interior wall panel of this embodiment includes, from bottom to top, a substrate, a permeation layer, an adhesive layer, and an aluminum veneer layer. The permeation layer is prepared by the following raw materials in parts by weight: 1000g modified polyurethane resin, 500g self-crosslinking silicone-acrylic emulsion, 65g nano silica, 510g reactive diluent, 46g silane coupling agent, 30g organic fluoride, 40g curing agent A, 30g photoinitiator, 30g dispersant, and 15g defoamer. The substrate is an asbestos-free fiber calcium silicate board with a thickness of 8mm. The modified polyurethane resin was prepared in Example 3. The self-crosslinking silicone-acrylic emulsion had a solid content of 50% and a nano-silica particle size distribution of 1-50 nm. The reactive diluent was tripropylene glycol diacrylate, the silane coupling agents included 30 g of silane coupling agent KH550 and 16 g of silane coupling agent KH560, the organofluorine compound was perfluorooctyltriethoxysilane, the curing agent A was epoxy curing agent T31, the photoinitiator was 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, the dispersant was sodium polyacrylate with a solid content of 40%, and the defoamer was an organosilicon defoamer with a solid content of 30%.
[0077] The adhesive layer is prepared by means of the following raw materials in parts by weight: Component A: 750g of polyether-type MDI-terminated polyurethane prepolymer, 80g of tackifier, 30g of antioxidant, 45g of toughening agent, and 0.8g of dibutyltin dilaurate; Component B: 131.5g of polyetheramine 230, 55.5g of adipic acid dihydrazide, and 1.0g of 2-ethyl-4-methylimidazolium. The polyether-type polyurethane prepolymer is a polyether-type MDI-terminated polyurethane prepolymer with an NCO content of 15% by mass; the tackifier is hydrogenated C9 petroleum resin with a softening point of 85℃; the antioxidant is antioxidant 1010; and the toughening agent is polyamide wax micropowder with a particle size of 1~5μm.
[0078] Everything else is the same as in Example 2.
[0079] Test results: The obtained metallic interior wall decorative panels were subjected to flexural strength and tensile strength tests. According to GB / T 7019-2024, the test results showed that: the average dry flexural strength was 31.0 MPa; the average saturated flexural strength was 29.0 MPa; the average tensile strength was 1.08 MPa; and the maximum single tensile strength was 1.21 MPa.
[0080] Example 4 The difference between this embodiment and embodiment 3 is as follows: The modified polyurethane resin was prepared in Example 4.
[0081] Everything else is the same as in Example 3.
[0082] Test results: The obtained metallic interior wall decorative panels were subjected to flexural strength and tensile strength tests. According to GB / T 7019-2024, the test results showed that: the average dry flexural strength was 31.8 MPa; the average saturated flexural strength was 29.8 MPa; the average tensile strength was 1.10 MPa; and the maximum single tensile strength was 1.23 MPa.
[0083] Example 5 The difference between this embodiment and embodiment 3 is as follows: The modified polyurethane resin was prepared in Example 5.
[0084] Everything else is the same as in Example 3.
[0085] Test results: The obtained metallic interior wall decorative panels were subjected to flexural strength and tensile strength tests. According to GB / T 7019-2024, the test results showed that: the average dry flexural strength was 32.5 MPa; the average water-saturated flexural strength was 30.5 MPa; the average tensile strength was 1.15 MPa; and the maximum single tensile strength was 1.26 MPa.
[0086] Comparative Example 1 The difference between this comparative example and Example 2 is as follows: The preparation method of the modified polyurethane resin in this comparative example includes the following steps: Under a nitrogen atmosphere, 800g of polypropylene glycol (number average molecular weight 4000), 56g of isophorone diisocyanate, and 0.9g of organotin catalyst were added sequentially to a dry reactor. The mixture was heated to 75°C and stirred for 4.5h. The temperature was then lowered to 65°C, and 200g of epoxy resin E-51 was added. The mixture was kept at this temperature and stirred for 2.5h. The temperature was then lowered to 50°C, and 13.4g of pentaerythritol triacrylate and 0.6g of p-hydroxyanisole were added. The temperature was then raised to 65°C, and the mixture was stirred for another 6h until the NCO content was below 0.5%. Heating was then stopped, and the mixture was cooled to room temperature to obtain the modified polyurethane resin.
[0087] The initial molar ratio (R value) of isocyanate groups to total hydroxyl groups is approximately 1.00.
[0088] Everything else is the same as in Example 2.
[0089] Test results: The obtained metallic interior wall decorative panels were subjected to flexural strength and tensile strength tests. According to GB / T 7019-2024, the test results showed that: the average dry flexural strength was 26.0 MPa; the average saturated flexural strength was 23.5 MPa; the average tensile strength was 0.82 MPa; and the maximum single tensile strength was 0.90 MPa.
[0090] Comparative Example 2 The difference between this comparative example and Example 2 is as follows: No tackifier was added to the adhesive.
[0091] Everything else is the same as in Example 2.
[0092] Test results: The obtained metallic interior wall decorative panels were subjected to flexural strength and tensile strength tests. According to GB / T 7019-2024, the test results showed that: the average dry flexural strength was 27.7 MPa; the average water-saturated flexural strength was 23.4 MPa; the average tensile strength was 0.85 MPa; and the maximum single tensile strength was 0.96 MPa.
[0093] Comparative Example 3 The difference between this comparative example and Example 2 is as follows: The preparation method of the modified polyurethane resin in this comparative example includes the following steps: Under a nitrogen atmosphere, 800g of polypropylene glycol (number average molecular weight 600), 310g of isophorone diisocyanate, and 1.0g of organotin catalyst were added sequentially to a dry reactor. The mixture was heated to 75°C and stirred for 5 hours. The temperature was then lowered to 55°C, and 36.5g of pentaerythritol triacrylate and 0.6g of p-hydroxyanisole were added. The mixture was heated to 65°C and stirred for another 6 hours until the NCO content was below 0.5%. Heating was then stopped, and the mixture was cooled to room temperature to obtain the modified polyurethane resin.
[0094] The initial molar ratio (R value) of isocyanate groups to total hydroxyl groups is approximately 1.00.
[0095] Everything else is the same as in Example 2.
[0096] Test results: The obtained metallic interior wall decorative panels were subjected to flexural strength and tensile strength tests. According to GB / T 7019-2024, the test results showed that: the average dry flexural strength was 26.3 MPa; the average saturated flexural strength was 22.5 MPa; the average tensile strength was 0.81 MPa; and the maximum single tensile strength was 0.90 MPa.
[0097] The test results above show that in Examples 1-5 and Comparative Examples 1-3, the modified polyurethane resin structure effectively improved the crosslinking density and rigidity of the resin, thereby directly and significantly enhancing the flexural strength of the decorative panel. The further introduction of methacryloyloxyethyl phosphate strengthened the interfacial bonding between the infiltration layer and the substrate, simultaneously improving the tensile strength and water resistance of the decorative panel. In contrast, Comparative Example 1, which used high-molecular-weight pure polyether to prepare the modified polyurethane resin, not only resulted in a significant decrease in the flexural strength of the decorative panel but also a marked reduction in the flexural strength under saturated water conditions. In Comparative Example 2, the lack of a tackifier led to insufficient interfacial bonding, resulting in a significant decrease in both tensile strength and water resistance. Comparative Example 3, which did not add epoxy resin E-51 to the modified polyurethane resin, lacked the support of rigid epoxy groups, resulting in a decrease in crosslinking density, reduced resin rigidity and interfacial compatibility, and a significant decrease in both dry flexural strength and tensile strength.
[0098] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A metallic-textured interior wall panel, characterized in that, From bottom to top, it includes a substrate, a diffusion layer, an adhesive layer, and a metal finish layer. The preparation of the permeation-enhancing layer includes the following raw materials in parts by weight: 80-120 parts of modified polyurethane resin, 40-60 parts of self-crosslinking silicone-acrylic emulsion, 4-8 parts of nano-silica, 40-60 parts of reactive diluent, 3-6 parts of silane coupling agent, 2-4 parts of organofluorine compound, 3-5 parts of curing agent A, 2-4 parts of photoinitiator, 2-4 parts of dispersant and 1-2 parts of defoamer; The preparation of modified polyurethane resin includes the following raw materials in parts by weight: The modified polyurethane resin comprises 70-80 parts of oligomeric polyol, 17-31 parts of diisocyanate, 15-20 parts of bisphenol A epoxy resin, 1.7-11 parts of polyhydroxy acrylate monomer, 0.05-0.1 parts of organotin catalyst, and 0.02-0.06 parts of polymerization inhibitor; the preparation method of the modified polyurethane resin includes the following steps: Under an inert atmosphere, oligomeric polyol, diisocyanate and organotin catalyst are mixed evenly, heated to 70-75℃ and reacted for 4-5 hours, cooled to 60-65℃, bisphenol A type epoxy resin is added, reacted for 2-2.5 hours, cooled, polyhydroxy acrylate monomer and polymerization inhibitor are added, heated to 65-70℃ and reacted for another 5-6 hours, cooled to obtain modified polyurethane resin; The oligomeric polyol is at least one of polyether polyol and polyester polyol, and its number average molecular weight is not higher than 1000. The adhesive layer is prepared by means of the following raw materials in parts by weight: Component A: 70-85 parts of polyether-type polyurethane prepolymer, 5-10 parts of tackifier, 2-4 parts of antioxidant, 3-6 parts of toughening agent, and 0.07-0.1 parts of organotin catalyst; Component B: 8.5-13 parts of polyetheramine, 4-5.5 parts of adipate dihydrazide and 0.1-0.15 parts of 2-ethyl-4-methylimidazole.
2. The metallic-textured interior wall panel according to claim 1, characterized in that, The polyhydroxy acrylate monomer is pentaerythritol triacrylate.
3. The metallic interior wall panel according to claim 1, characterized in that, The raw materials of the modified polyurethane resin also include 2 to 4 parts by weight of phosphate ester-containing acrylate monomers.
4. The metallic interior wall panel according to claim 1, characterized in that, In the preparation method of the modified polyurethane resin, after adding the polyhydroxy acrylate monomer, the method further includes the step of adding an acrylate monomer containing a phosphate ester.
5. The metallic-textured interior wall panel according to claim 1, characterized in that, The reactive diluent is either isobornyl acrylate or tripropylene glycol diacrylate.
6. The metallic-textured interior wall panel according to claim 1, characterized in that, The polyether-type polyurethane prepolymer is a polyether-type MDI-terminated polyurethane prepolymer with an NCO content of 10%~15%.
7. The metallic-textured interior wall panel according to claim 1, characterized in that, The thickener is petroleum resin.
8. A method for preparing a metallic-textured interior wall panel as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1: After mixing nano-silica, dispersant and part of reactive diluent, add modified polyurethane resin, self-crosslinking silicone-acrylic emulsion, the remaining reactive diluent, silane coupling agent, organofluorine compound and defoamer, add curing agent A and photoinitiator, mix evenly to obtain the penetration-enhancing coating. S2: At 90~100℃, the polyether-type polyurethane prepolymer, tackifier, antioxidant, toughening agent and organotin catalyst are mixed evenly to obtain component A; the polyetheramine, adipate dihydrazide and 2-ethyl-4-methylimidazolium are mixed evenly to obtain component B; before use, component A and component B are mixed evenly to obtain the adhesive. S3: After pretreating the substrate, the infiltration layer coating is evenly applied to the substrate surface and cured to obtain the infiltration layer; S4: Apply adhesive to the surface of the permeation layer, attach the metal finishing layer, hot-press to bond, and then perform post-treatment to obtain the final product.
Citation Information
Patent Citations
Heat preservation and decoration integrated plate with three-dimensional metal veneer and manufacturing method thereof
CN111761889A
Hot-pressed aluminum composite decorative plate and preparation method thereof
CN121019055A
Water-borne woodware coating containing modified polyurethane emulsion and preparation method thereof
CN105368291A
Substrate product with metal texture and manufacturing method thereof
CN109750260A